The legend of the fog - Mikkigak, Qaunak, 1932-; Schwartz, Joanne; Christopher, Danny (Iqaluit, Nunavut : Inhabit Media, 2017)
"In the spring, the Arctic tundra is bursting with life. Plants and animals have endured a long, bitter winter, waiting for their chance to peek out through the deep snow. But there are also dangers lurking on the tundra in dark caves and beyond distant hills; creatures that hunters hope never to encounter lying in wait. When a lone hunter named Qaunngauvaniq takes a walk on the spring tundra, his journey soon becomes a life-or-death struggle when he meets one of the tundra's most fearsome, and hungry, inhabitants-a deadly tuurngaq! Written by Cape Dorset elder Qaunaq Mikkigak and highly acclaimed picture book author Joanne Schwartz, The Legend of the Fog bring a centuries-old Inuit traditional tale to life for modern readers."--
Ages 7-10
Keywords: Storytelling -- Inuit -- Children's literature; Inuit; Oral tradition -- Nunavut -- Children's literature